Domestic transmission of Rift Valley Fever virus in Diawara (Senegal) in 1998 - Laurence Marrama (2018)
In 1998, circulation of the Rift Valley Fever (RVF) virus was revealed in Diawara by detection of IgM antibodies in sheep and isolation of the virus from mosquitoes caught outside a village. A seroprevalence study was carried out. Finger-prick blood samples, individual and collective details were obtained. One thousand five hundred twenty people (6 months - 83 years) were included. Overall prevalence in this group was approximately 5.2%. The prevalence in infants (6 months-2 years) was 8.5%. Age, gender, contact with a pond, presence of sheep, and abortion among sheep, and individual or collective travel history were not statistically associated with prevalence. Prevalence increased significantly when the distance to a small ravine, located in the middle of the village, decreased. The results suggest a low, recent, not endemic circulation of the virus. Culex quinquefasciatus was captured near the ravine. This mosquito, similar to Culex pipiens, can play a similar role in human-to-human transmission of the RVF virus.